Impact of cell wall adsorption behaviours on phenolic stability under air drying of blackberry with and without contact ultrasound assistance. (April 2023) - Gong, Wenjin; Zhao, Xinyu; Manickam, Sivakumar; Liu, Xuwei; Li, Dandan; Han, Yongbin; Kiani, Hossein; Feng, Chaohui; Tao, Yang
Abstract: The physicochemical properties of blackberry cell walls under air drying with and without contact ultrasonication were analysed, and their ability to bind soluble phenolics was evaluated. Compared to air drying alone, ultrasound promoted cell wall shrinkage and reduced their specific surface area and water binding capacity. Meanwhile, the in-process ultrasound further increased the amount of water soluble pectin (WSP) and decreased protopectin. After drying, the cell walls of ultrasound-dried samples contained 11.6% less protopectin (PP) than air-dried samples. Pectins in ultrasound-dried samples were also more aggregated with a reduced branching degree of Rhamnogalacturonan-I (RG-I). Most of these ultrasonic modifications of blackberry cell walls hindered their phenolics acquirement. The equilibrium adsorption capacities of cell walls from ultrasound-dried blackberries for 1 h were 33.5% (for catechin) and 21.8% (for phloretic acid) lower than the counterparts from air-dried samples for 8 h. Although the soluble phenolics absorbed by dried blackberry cell walls were more thermal-stable than those adsorbed by fresh blackberry cell walls, the overall protection provided by cell walls was still regarded as attenuated with drying due to the decline in the adsorption ability. Besides, it is believed that the higher retention of soluble phenolics in ultrasound dried samples is ascribed to the shortened thermal-drying time rather than the cell walls-phenolics interactions. These findings provide an in-depth understanding of the effect of ultrasound drying on phenolic stability. Graphical abstract: Image 1 Highlights: Ultrasound reduced specific surface area and water binding capacity of cell walls. Ultrasound increased the amount of water soluble pectin and decreased protopectin. The ultrasound-intensified drying decreased the branching degree of RG-I pectin. The ability of cell walls to absorb soluble phenolics was reduced after sonication. The protections on soluble phenolics provided by cell walls weakened with drying.